If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6(p + -3) = -4 Reorder the terms: 0.6(-3 + p) = -4 (-3 * 0.6 + p * 0.6) = -4 (-1.8 + 0.6p) = -4 Solving -1.8 + 0.6p = -4 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '1.8' to each side of the equation. -1.8 + 1.8 + 0.6p = -4 + 1.8 Combine like terms: -1.8 + 1.8 = 0.0 0.0 + 0.6p = -4 + 1.8 0.6p = -4 + 1.8 Combine like terms: -4 + 1.8 = -2.2 0.6p = -2.2 Divide each side by '0.6'. p = -3.666666667 Simplifying p = -3.666666667
| 100+n=324 | | -26(x-90)=x+81 | | 0.1x=4.5 | | 147-5x=22x+24 | | -5x+2y=6 | | 15x-10=15x-10 | | 2x+x+x-20=180 | | 7=9d+7-5d | | 14+3g=8g-3(g-4) | | 4x+3x-8=13 | | 9x+35=4x | | 7x+1=8x-3 | | 9x+3=8x+7 | | -2(2v-4)=-4(-v+2) | | x-.16=.66 | | 144=h(8+16) | | 4c-8-c=7 | | 3x+5=3x-15 | | -2j(j-3)=2j+6 | | x+23=17 | | 2(8-1)+8+7=x | | 40=6y+y-3y | | 2y+14=2(2y-1) | | 8a-3a-a=32 | | z+8=522 | | 3(-4+x)=3x-12 | | -70g=4200 | | 12y+5-3y=41 | | -80g=4200 | | 6x+197=14x-11 | | 69-3x=42x+19 | | 0.66p=4.62 |